The development of health literacy factors and their impact on national minorities in the Slovenian-Italian border region - Krmac, Nina (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2019)
The article presents the results of the research on development of health literacy factors among members of the Slovenian and Italian national minorities in the Slovenian-Italian border region. It included 186 respondents, who have always lived in the traditional area of their minority and have not moved beyond the state border. Through quantitative analysis, the authors established that both minorities have higher level of health literacy compared to the rest of population. Age has an important role in understanding medical documentation and information, as does education on understanding of instructions for taking medicines and maintaining health. The resulting predictor, preventing and identifying disease symptoms, suggests that members of the national minorities should be better trained in healthy lifestyle.
Keywords: funkcionalna pismenost; Italija; italijanska manjšina; Slovenija; slovenska manjšina; zdravstvena pismenost